The Detrimental Effects of the Internet in Today's World: A Comprehensive Analysis (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The internet, a transformative innovation of the 20th century, has revolutionized the way society communicates, learns, and interacts. However, the widespread use of the internet in today's world has brought about a range of negative consequences that deserve careful consideration. This article provides an in-depth exploration of the bad effects of the internet on various aspects of human life, including mental health, privacy, misinformation, and social relationships. By critically examining these issues, we aim to foster a better understanding of the challenges posed by the internet and encourage the development of strategies to mitigate its negative impacts.